Traditional knowledge and sustainable agarwood cultural practices among Indonesian ethnic communities - Royyani, Mohammad Fathi; Rachmat, Henti; Christita, Margaretta; Fajar, Abbas Sofwan; Milyardi, Indra; Hakam, Saiful; Arra’d Sofianto, Imran; Kusumadewi Sri Yulita; Fifi Gus Dwiyanti; Asep Hidayat; Tien Wahyuni; Susana Yuni Indriyanti; et al. (Ethnobotany Research and Applications, 2026)
Background: Gaharu, also referred to as oud or agarwood (Aquilaria spp.), is one of the oldest fragrant substances, possessing profound cultural and economic importance. The historical utilization of agarwood by several ethnic groups globally has been recorded since ancient times. The elevated global demand for agarwood has resulted in problems like overharvesting, exploitation, and illegal trade that are threatening natural populations and market sustainability. There is also a lack of information on the traditional knowledge of indigenous people or ethnic groups involved in collecting and utilizing agarwood. This research is an attempt to explore the sustainability of agarwood cultural practice among generation of ethnic communities and empirical scientific evidence support their uses. We determined variable grading criteria (smell, resin color and density/texture) in different ethnic communities across the islands and show how home-garden cultivation enables a sustainable supply in accordance with ritual longing. Methods: Ethnoecological studies were conducted based on in-depth interviews carried out with 2-13 key informants for each ethnic communities across Indonesia archipelago (main islands of Indonesia, i.e. Sumatra, Java, Kalimantan, Nusa Tenggara, Sulawesi, Maluku and Papua). Results: This article reveals the ethnobotanical diversity of agarwood, reflected in variations in naming, use, and perspectives across ethnic groups in Indonesia. These findings demonstrate that agarwood is not merely an economic commodity but has been deeply integrated into an embodied cultural entity. The convergence of ethnographic data with historical sources—both Nusantara manuscripts and colonial records-confirms that knowledge and use of agarwood have been ongoing for a long time. The interdisciplinary approach in this study demonstrates the alignment between traditional practices, such as medicinal uses, and scientific evidence regarding the chemical composition of agarwood. Furthermore, despite declining natural availability due to deforestation, agarwood remains sustainable through cultivation efforts. This practice is driven not only by commercial value but also by cultural and religious needs, confirming the continued role of agarwood in the socio-cultural system of society Conclusion: The cultural significance of agarwood utilization in ethnic communities should not be overlooked, and this knowledge is a national heritage. And we need scientific evidence to support the anecdotal evidence of those traditional practices. Keywords: Agarwood, Indonesia, local community, traditional knowledge